2014
DOI: 10.1523/jneurosci.0521-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Associative Encoding and Retrieval Are Predicted by Functional Connectivity in Distinct Hippocampal Area CA1 Pathways

Abstract: Determining how the hippocampus supports the unique demands of memory encoding and retrieval is fundamental for understanding the biological basis of episodic memory. One possibility proposed by theoretical models is that the distinct computational demands of encoding and retrieval are accommodated by shifts in the functional interaction between the hippocampal CA1 subregion and its input structures. However, empirical tests of this hypothesis are lacking. To test this in humans, we used high-resolution fMRI t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 51 publications
8
98
0
Order By: Relevance
“…Furthermore, recent high-resolution imaging has also suggested that the CA1 subfield and neocortical-to-CA1 connectivity are important to memory retrieval success (Brown et al, 2014; Duncan et al, 2014). Because CA1 area receives input from parahippocampal cortex via entorhinal cortex and the temporoammonic pathway (Amaral & Insausti, 1990), one possibility is that CA1 may play a role in anchoring new visuospatial input onto existing templates (see also: J.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent high-resolution imaging has also suggested that the CA1 subfield and neocortical-to-CA1 connectivity are important to memory retrieval success (Brown et al, 2014; Duncan et al, 2014). Because CA1 area receives input from parahippocampal cortex via entorhinal cortex and the temporoammonic pathway (Amaral & Insausti, 1990), one possibility is that CA1 may play a role in anchoring new visuospatial input onto existing templates (see also: J.…”
Section: Discussionmentioning
confidence: 99%
“…1). Entorhinal cortex (EC) was omitted from analyses due to imaging signal dropout, an issue present in other high-resolution imaging studies targeting the MTL using similar MRI acquisition sequences (e.g., Duncan, Tompary, & Davachi, 2014). In accordance with the methodology from other high-resolution fMRI projects, the “CA3/DG” ROI was defined to include subfields CA3, CA2 and DG because spatial resolution limitations prevent finer division (Chen, Olsen, Preston, Glover, & Wagner, 2011; Ekstrom et al, 2009; LaRocque et al, 2013; Zeineh et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…There are several approaches for dealing with this issue (Friston et al, 1997; Rissman et al, 2004). Here we adopt a “background connectivity” approach in which stimulus-evoked responses and noise sources are projected out of the data and correlations are calculated in the residuals during different experimental conditions (Al-Aidroos et al, 2012; Griffis et al, 2015; Norman-Haignere et al, 2012; Duncan et al, 2014; Tompary et al, 2015). The resulting connectivity reflects spontaneous, intrinsic interactions within the functional networks engaged by each condition.…”
Section: Introductionmentioning
confidence: 99%
“…Although images taken at a high field strength are able to offer detailed insight into hippocampal subfields, high-field scanners are not yet common in clinical or research settings, so 7T and 9.4T protocols currently have limited applicability. Similar protocols have been developed for images collected on 3T and 4T scanners 11,20,21,23,24,25,28,33 . Many of these protocols are based on images with sub-1mm voxels voxel dimensions in the coronal plane, but have large slice thicknesses (0.8-3 mm) 11,20,21,23,25,28,33 or large inter-slice distances 20,28 , both of which result in a significant measurement bias in the estimation of volumes of the individual subfields.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these protocols are based on images with sub-1mm voxels voxel dimensions in the coronal plane, but have large slice thicknesses (0.8-3 mm) 11,20,21,23,25,28,33 or large inter-slice distances 20,28 , both of which result in a significant measurement bias in the estimation of volumes of the individual subfields. Additionally, many of the existing 3T protocols exclude subfields in all or part of the hippocampal head or tail 20,23,25,33 or do not provide detailed segmentations of important substructures (i.e., combine the DG with CA2/CA3 or do not include the strata radiatum/lacunosum/moleculare of the CA) 11,20,21,23,24,25,28,33 . There is therefore a need in the field for a detailed description of a protocol that can reliably identify relevant subfields throughout the head, body, and tail of the hippocampus that is based on a scanner commonly available in clinical and research settings.…”
Section: Introductionmentioning
confidence: 99%